P645 Peruvian gonococcal strains reveal novel NG-MAST types and false-positive β-lactamase isolates with blatem gene mutations. (14th July 2019) - Van, Adriana Le; Rahman, Nazia; Dozier, Nelson; Gann, Patrick Mc; Regeimbal, James; Mccoy, Andrea; Soge, Olusegun; Garges, Eric; Jerse, Ann
Abstract : Background: The Global Emerging Infectious Surveillance Program of the U.S. Department of Defense, Armed Forces Health Surveillance Branch supports a repository for Neisseria gonorrhoeae (GC) clinical isolates recovered from routine care at U.S. Military Treatment Facilities in the continental US (CONUS) and at several overseas (OCONUS) labs though collaborative surveillance projects. Here we report the use of phenotypic data in conjunction with molecular typing and whole genome sequencing (WGS) of GC to describe the antimicrobial resistance trends from isolates collected from three geographically different clinics in Lima, Callao and Iquitos, Peru. Methods: Putative GC collected from patients between 2012 and 2015 were confirmed as GC using standard biochemical and serological methods. Susceptibility to eight different antibiotics was determined by Etest. β-lactamase (ßL) activity was determined by nitrocefin hydrolysis. NG-MAST types were determined by standard methods and WGS analysis. Results: Sixty eight out of 90 isolates examined were confirmed as GC. Antimicrobial susceptibility testing showed a high level of resistance to ciprofloxacin (70%) and lower percentages of resistant strains to other common antibiotics. Although 63% percent of isolates were β-lactamase positive by the nitrocefin test, only 70% of these isolates were Pen R . The other 30% had reduced susceptibility to Pen (Pen RS ). Whole Genome Sequencing (WGS) revealed mutations in the bla TEM-1B gene for these Pen RS isolates. These isolates were collected from different clinics, but showed genetic relatedness based on nucleotide polymorphism (SNP)-based analysis. Several novel NG-MAST types were detected among the isolates. Conclusion: These findings highlight the high prevalence of multidrug resistant GC in Peru. The identification of NG-MAST types not identified in surveillance reports from Europe or the United States is important. Further, WGS allowed us to discern false positive β-lactamase isolates by detecting mutations in the bla TEM genes observed in Pen RS isolates and showed the clonally relatedness of these isolates. Disclosure: No significant relationships.